Environmental DNA-based metabarcoding reveals a high animal biodiversity level within Red Sea mangrove beds - Mohammed-Geba, Khaled; Elamin, Ahmed Mohamed; Hassan, Arwa; Mohammed, Essmat; Salah-Eldin, Alaa-Eldin; Schott, Eric J.; Galal-Khallaf, Asmaa (Frontiers in Marine Science, 2025)
IntroductionMangroves play a vital role in stabilizing coastlines, supporting biodiversity, and delivering essential ecosystem services.MethodsTo assess animal biodiversity in Avicennia marina (grey mangrove) habitats along Egypt’s Red Sea governorate’s coast, seawater samples were collected for environmental DNA (eDNA) analysis from six key mangrove sites: 17 km and 40 km south of Safaga City, El-Sharm El-Bahary, Wadi El-Gemal, El-Qolaan, and Hamata. For comparison, eDNA was also obtained from two non-mangrove sites in the same region. The eDNA was analyzed via COI gene metabarcoding, and diversity metrics were used to compare habitats.ResultsThirteen fish species were identified as exclusive to mangroves, alongside diverse arthropods, poriferans, and cnidarians. Moolgarda sp. (mullets) and Psettodes erumei (Indian halibut) were the most abundant fish species detected. Relative read abundances differed significantly between mangrove and non-mangrove sites, with some species exhibiting dual habitat use (e.g., transitioning between coral and mangrove systems). Diversity and evenness indices showed that biodiversity in mangrove habitats, especially Wadi El-Gemal location, overtook that in non-mangrove locations. Notably, DNA from two marine alien species could be identified, i.e., Anthopleura fuscoviridis (Cnidaria) in a mangrove site, and Callinectes sapidus (Decapoda) in non-mangrove sites. The presence of C. sapidus could be verified by conventional PCR.DiscussionThis study underscores the high biodiversity supported by Red Sea mangroves, emphasizing their ecological and economic value. These findings can inform sustainable management strategies to protect these critical ecosystems for future generations.